Serious Games to Enhance Education. Play, Technology and Archaeology in a Spanish museum - María José Merchán; Pilar Merchán; Emiliano Pérez (Universidad Pedagógica Nacional, 2023)
Serious games are a powerful resource in the teaching-learning process in formal and informal learning settings since this kind of activity motivates participants to take part actively in their own learning process. Within informal learning environments, they serve to improve their pedagogical role, which is sometimes difficult to be perceived by users. Nevertheless, serious games play another equally important role in museums, Art galleries or Science centres: engaging part of the surrounding society with this kind of institutions. This paper describes a "serious game" using new technology that includes Information and Communication Technologies and 3D digitized models to be played in informal learning settings. It aims to enhance their didactic role and look for social engagement. An experimental experience was carried out in the National Museum of Roman Art (Mérida, Spain) to attract and retain a specific group of people, teenagers, reluctant to visit archaeological museums most of the time since they considered them boring places. Finally, this experience served to assess the applicability and versatility as an educational resource of the game scheme proposed.